A cluster randomized trial comparing photoaging app and school based educational intervention for tobacco use prevention in adolescents - Tamadhir Al-Mahrouqi; Fida Al-Ghailani; Maryam Al-Maqbali; Maather Al Saidi; Gowda Parameshwara Prashanth (Scientific Reports)
Abstract Adolescent tobacco use is a major public health concern, particularly in sociocultural contexts like Oman, where smoking among males is prevalent. This study evaluates two interventions: a photoaging app (PA) and a school-based educational module (SBM), designed to improve knowledge, attitudes, and behaviors toward tobacco use in adolescent males. A cluster randomized trial was conducted among public school boys (grades 9–12) in North Al Batinah, Oman. Schools were randomized to receive either PA or SBM interventions. PA used a smartphone app to simulate photoaging effects of smoking, while SBM employed culturally adapted modules based on WHO’s Tobacco Health Hazards Toolkit. Pre- and post-intervention assessments included tobacco knowledge, susceptibility scores, and attitudes. A total of 227 students participated. Both interventions significantly improved perceptions of tobacco harm and reduced susceptibility to tobacco use. PA showed a greater effect on enhancing perceptions of harm (OR 2.05, 95% CI 1.31–3.20, p = 0.002), while SBM was more effective in fostering support for smoking bans (p = 0.065). Differences in susceptibility were not statistically significant between groups. Both interventions demonstrated effectiveness, with PA excelling in personalized risk communication and SBM promoting community-oriented tobacco control. Hybrid approaches could optimize adolescent tobacco prevention strategies. Trial registration: NCT06483763 (ClinicalTrials.gov).